2015
DOI: 10.1021/acs.jpcc.5b03357
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Wedge Scheme to Describe Intermolecular Proton-Coupled Electron Transfer through the H-bond Complex Formed Between a Phenylenediamine-Based Urea and 1,8-Naphthyridine

Abstract: Recently we introduced the "wedge scheme" as a convenient means to include H-bonded intermediates in an overall proton-coupled electron transfer (PCET) mechanism by showing that it can nicely explain the unusual solvent-and concentrationdependent voltammetry of a phenylenediamine-based urea, U(H)H. This compound undergoes an apparent 1 e − reversible oxidation in CH 2 Cl 2 that actually corresponds to 2 e − oxidation of half of the ureas to the quinoidal cation accompanied by transfer of a H + and deactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…This can be an intramolecular H-bond, but it also could be an intermolecular H-bond. In the latter case the bimolecular reactions forming the H-bond complex are integral to the overall reaction and need to be considered in the overall kinetic analysis. , To do this, several years ago we introduced the “wedge scheme” mechanism, Scheme b, in which the bimolecular reactions forming and breaking the H-bond intermediate with and without PT are displayed along a third axis perpendicular to the ET–PT square. , This clearly defines an alternative pathway for ET, shown by the red horizontal line, that corresponds to ET and possibly PT within the H-bond complex. It is straightforward to show that the formal electrode potential for this reaction, E °′(AHB + /AHB), falls in between that for the fully protonated redox couple (AH + /AH) and that for the fully deprotonated couple (A/A – ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be an intramolecular H-bond, but it also could be an intermolecular H-bond. In the latter case the bimolecular reactions forming the H-bond complex are integral to the overall reaction and need to be considered in the overall kinetic analysis. , To do this, several years ago we introduced the “wedge scheme” mechanism, Scheme b, in which the bimolecular reactions forming and breaking the H-bond intermediate with and without PT are displayed along a third axis perpendicular to the ET–PT square. , This clearly defines an alternative pathway for ET, shown by the red horizontal line, that corresponds to ET and possibly PT within the H-bond complex. It is straightforward to show that the formal electrode potential for this reaction, E °′(AHB + /AHB), falls in between that for the fully protonated redox couple (AH + /AH) and that for the fully deprotonated couple (A/A – ).…”
Section: Introductionmentioning
confidence: 99%
“…28 In our earlier reports, we showed that the wedge scheme could explain the electrochemistry of a rather unique PCET reaction occurring with the phenylenediamine−urea derivative, UHH, in aprotic solvents. 15,16 In this study, we extend its application to a more general PCET reaction involving the second oxidation of a simple phenylenediamine derivative in the presence of weak bases in acetonitrile. Furthermore, we investigate the stepwise or concerted nature of the ET and PT within the H-bond intermediate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The electrochemical behavior of quinones and phenylenediamines are sensitive to the presence of acids, [4b,c, 5] bases, [6] hydrogen donors, [1, 4n, 5a,f,i-k, 7] and hydrogen-acceptors [6,8] (defined Voltammetry experiments were performed on 1,4-benzoquinone and 1,4-phenylenediaminei na cetonitrile, propionitrile (from five commercial suppliers:A cros Organics,A ldrich, Alfa Aesar,F luka, and Merck), and butyronitrile,t ow hich different electrochemical responses were collected acrosst he three nitrile solvents and within the five commercial brands of propionitrile, owing to the reduced (1,4-benzoquinone) or oxidized (1,4-phenylenediamine) compounds reacting with impurities in the solvents. Of the three solvents, propionitrile suffered from the most impurities, which adversely affected the electrochemical results.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical behavior of quinones and phenylenediamines are sensitive to the presence of acids,, bases, hydrogen donors,,, and hydrogen‐acceptors (defined as compounds that participate in hydrogen‐bonding interactions without any protons transferred) and will deviate from the typical EE behavior according to the extent and type of the interaction. Quinones can function as hydrogen acceptors and interact with hydrogen donors such as alcohols, which, when so doing, will shift E Q1 and E Q2 to less negative potentials with a concomitant decrease in Δ E Q =| E Q1 − E Q2 | ,.…”
Section: Introductionmentioning
confidence: 99%
“…From the above discussion, more information is required about the conditions driving H-bonded systems into proton transfer reactions to fully understand anion recognition processes by these urea derivatives. Also, such a study would complement the growing interest in elucidating H-bonding effects on PCET reactions. ,, Dihomooxacalix[4]­arene bidentate ureas are interesting H-bond donor species ((HD) 2 -R 2 ) for studying anion recognition, as previous results have shown that they noticeably increase their binding capacity to anions when the nature of the substituent groups in their structures is changed (from t -Bu to Ph, K b ranges from ∼250 to ∼7000 M –1 , respectively). , Also, by electrogenerating dianions ([NO 2 – ϕ – NO 2 ] 2– ) from dinitrobenzene compounds (NO 2 – ϕ – NO 2 ), electron transfer-controlled hydrogen bonding (ETCHB) can be studied, , leading to increases in the binding affinity when the charge state of the receptor is changed. ,,, ETCHB processes between these latter species can be generally described by the next set of chemical equations: , …”
Section: Introductionmentioning
confidence: 99%